A van der Waals heterojunction based on monolayers of MoS2 and WSe2 for overall solar water splitting. Issue 13 (14th May 2022) - Dalla Valle, Paul; Cavassilas, Nicolas
Abstract : We numerically investigated a complete system for overall water splitting based on TMDC heterojunctions. We found a solar-to-hydrogen efficiency higher than 15% under realistic operating conditions. Abstract : Solar water splitting (SWS) has been widely studied as a promising technology for generating carbon-free hydrogen. In this article, we propose an unassisted SWS system based on van der Waals heterojunctions using monolayers of transition metal dichalcogenides as active core materials. This architecture, with its small band gap materials and high surface/volume ratio, has an intrinsic type-II band alignment that offers many advantages, such as direct Z-scheme configuration and wide absorption. To estimate the solar-to-hydrogen (STH) efficiency of the system, we developed a multiphysics model. While electronic and optical properties are computed with ab initio calculations, we implemented the detailed balance method and the Butler–Volmer kinetics to simulate the photoelectrochemical behaviour. Under realistic operating conditions, the system achieves a STH efficiency greater than 15%, which is higher than the critical 10% efficiency required to make SWS economically viable. Since our system is wireless and requires simple manufacturing processes (exfoliation), this result is remarkable.